2016
DOI: 10.2139/ssrn.2827152
|View full text |Cite
|
Sign up to set email alerts
|

Low Test Scores in Latin America: Poor Schools, Poor Families, or Something Else?

Abstract: Latin American students consistently score low on international tests of cognitive skills. In the PISA 2012 results, students in seven Latin I. IntroductionIn a recent analysis of on economic growth in Latin America, Hanushek and Woessmann [2012] argue that growth rates have been low despite increases in average levels of schooling because students' cognitive skills are "truly dismal." They show that student scores on mathematics and science tests are considerably lower in Latin America than in other countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In Latin America, the average result obtained in the PISA assessments is lower than the average obtained in other countries in which educational standards are similar; thus, the latent inequality in the socioeconomic conditions within most countries of this region plays an important role in the results of this evaluation [4]. In the case of Peru, it is observed that family wealth is more relevant compared to the parental educational attainment in terms of its relation to the academic performance demonstrated through the MARA score [3].…”
Section: State Of the Artmentioning
confidence: 70%
“…In Latin America, the average result obtained in the PISA assessments is lower than the average obtained in other countries in which educational standards are similar; thus, the latent inequality in the socioeconomic conditions within most countries of this region plays an important role in the results of this evaluation [4]. In the case of Peru, it is observed that family wealth is more relevant compared to the parental educational attainment in terms of its relation to the academic performance demonstrated through the MARA score [3].…”
Section: State Of the Artmentioning
confidence: 70%
“…Subsequently, I estimate the effect of socioeconomic and other characteristics on test scores separately by ethnic group to see how these characteristics affect student scores across groups. This is the same approach used in Breton and Canavire-Bacarreza [2017] to explain the much lower test scores in Latin America compared to Scandinavia. The results from the ethnicgroup-specific analysis provide more disaggregated information about how socioeconomic and other characteristics affect student scores differently in different ethnic groups.…”
Section: Methodology Used To Evaluate the Pisa Resultsmentioning
confidence: 96%
“…Even Vietnam, which is a very poor country with low average levels of adult schooling, has impressively high average scores on the PISA mathematics test. Breton and Canavire-Bacarreza [2017] investigate why Latin American countries had average scores on the PISA 2012 mathematics test that are 100 points below the average scores in Scandinavian countries. Families in Latin America have a much lower average level of schooling.…”
Section: The Hypothesismentioning
confidence: 96%